2023
DOI: 10.1161/strokeaha.123.042644
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prehospital Assessment by Paramedics and In-Hospital Assessment by Physicians in Suspected Stroke Patients: Results From 2 Prospective Cohort Studies

Abstract: Background: It is unknown if ambulance paramedics adequately assess neurological deficits used for prehospital stroke scales to detect anterior large-vessel occlusions. We aimed to compare prehospital assessment of these stroke-related deficits by paramedics with in-hospital assessment by physicians. Methods: We used data from 2 prospective cohort studies: the LPSS (Leiden Prehospital Stroke Study) and PRESTO study (Prehospital Triage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…When differentiating between NPE‐right and NPE‐left, no significant difference was found between the detection of LAVO right or LAVO left. Although the sensitivity is rather low for a test performed by neurologists, it is in the upper range of results from other LAVO tests conducted by EMS (Dekker et al., 2023 ). Because the NPE test is simple to understand and easy to apply without neurological expertise, we speculate that EMS may be able to replicate neurologists’ results to a similar extent.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…When differentiating between NPE‐right and NPE‐left, no significant difference was found between the detection of LAVO right or LAVO left. Although the sensitivity is rather low for a test performed by neurologists, it is in the upper range of results from other LAVO tests conducted by EMS (Dekker et al., 2023 ). Because the NPE test is simple to understand and easy to apply without neurological expertise, we speculate that EMS may be able to replicate neurologists’ results to a similar extent.…”
Section: Discussionmentioning
confidence: 87%
“…However, two or more tasks are typically required to test for aphasia and neglect, respectively (Lima et al., 2016 ; Pérez de la Ossa et al., 2014 ; Teleb et al., 2017 ), making the assessment complex and time‐consuming. Appropriately, it has recently been shown that aphasia and neglect—as assessed with a validated prehospital severity score by EMS—had the weakest correlations with the corresponding NIHSS items “Best Language” and “Extinction/Inattention” assessed by trained physicians in the emergency department (Dekker et al., 2023 ). To improve this unsatisfactory situation, we propose the NPE test as a simple, dichotomous, short, and easy‐to‐remember test that does not require any additional materials or a long observation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation